SME-4-producing Serratia marcescens from Argentina belonging to clade 2 of the S. marcescens phylogeny. (16th April 2019) - Dabos, Laura; Patiño-Navarrete, Rafael; Nastro, Marcela; Famiglietti, Angela; Glaser, Philippe; Rodriguez, Carlos H; Naas, Thierry
Abstract: Background: SME carbapenemases are increasingly reported, especially from North and South America. Here, we describe an SME-4-producing Serratia marcescens (SME -Sm ) clinical isolate from Argentina and compare its genome with other SME -Sm and Sm isolates recovered from public databases. Methods: Sm isolates were characterized by WGS using Illumina technology, susceptibility testing and MIC determination. Carbapenemase activity was revealed by biochemical tests based on imipenem hydrolysis. A whole-genome phylogeny was estimated for all the Sm isolates retrieved from public databases with kSNP3 and a whole-genome phylogenetic analysis based on non-recombinant core SNPs was inferred for Sm complete genomes and for those encoding any bla SME variants. Results: Sm 163 was resistant to amoxicillin, temocillin, aztreonam and carbapenems, remaining susceptible to extended-spectrum cephalosporins. WGS analysis of Sm 163 revealed a genome of 5139329 bp and a chromosomally encoded bla SME-4 carbapenemase gene located on a genomic island closely related to SmarGI1-1 of Sm N11-02820. Comparison of the Sm genomes revealed that the 14 SME -Sm isolates possess this genomic island inserted at the same loci, that 13/14 belong to clade 1 and that 11/14 form a well-defined subcluster of cluster I of Sm clade 1, while Sm 163 belongs to clade 2, suggesting that an SME-encoding genomic island may have been transferred between isolates from different clades. Conclusions: To the best of our knowledge this is the first report of an SME-4-encoding Sm from Argentina. The bla SME-4 gene is located on a SmarGI1-1-like genomic island. The genome of Sm 163 belongs to clade 2, unlike all the other SME -Sm isolates, which belong to clade 1.